Penerapan Metode Snowball Throwing Berbantuan Media Audio Visual dalam Meningkatkan Hasil Belajar IPS Siswa Kelas IV - Kurniasari, Rizky; Rezania, Vanda (UNIB Press, 2022)
The purpose of this study was to determine the improvement of students' social science knowledge competence through conventional learning methods with the Snowball Throwing learning method assisted by audio-visual media in fourth grade students of SDN Banjarpanji. This research is included in classroom action research (CAR) with two cycles. The subjects of this study were fourth grade students at SDN Banjarpanji. The number of fourth grade students at SDN Banjarpanji is 13 students. Data collection techniques used in this study were observation, interviews, documentation, and tests. The results obtained from the pre-cycle activities showed that the percentage of classical learning completeness was 30.7%. Cycle I with the percentage of classical learning completeness 38.4%, while in the second cycle the percentage of classical learning completeness is 100%. To compare two paired samples, the researcher used Paired Sample T-Test as data analysis. It can be seen that there is a significant difference between the two learning methods of 0.237. Thus, it can be concluded that the Snowball Throwing learning method assisted by audio-visual media can improve social studies learning outcomes for fourth grade students at SDN Banjarpanji.